DIFABLE PERCEPTION FOR ACCESSIBILITY AND INFORMATION OF PUBLIC TRANSPORT IN JAKARTA - Mochdiana Hernawan (Journal of the Civil Engineering Forum, 2012)
Every human being has equal right for accessing to the transportation. Difable persons that have different ability also have the same right. The provision of the accessibility and information facility in public transport is not fully meet difable need and therefore difable persons have difficulties in accessibility and information while using public transports. This research will investigate the difable perceptions about accessibility and traveler information for the public transport in Jakarta. Questionnaire method will be used for this purpose and then analyzed by Importance Performance Analysis. The improvement for the transport infrastructure and information system will be elaborated. The findings of the research could be used as input for the local authority while planning or re-construction public transport infrastructure and information system so that difable persons become more accessible and convenience. The study results show that the average value of the perceived performance for the accessibility is 2.78 from 5 scales. This means the performance of the accessibility in overall is fairly. For the information facility, the average performance is 3.11 that meaning the performance in overall is good. The respondents required the provision of waiting room for difable persons as a priority. The information about the departure of the vehicle should been improved as priority to be increased. Furthermore, it is obtained that the Customer Satisfaction Index (CSI) value for accessibility is 56%. This indicates the entire respondents satisfied sufficiently with the accessibility facility. Also, 62% of the CSI value shows that the respondents satisfied sufficiently with the provided information.